Methylation status and DNase I sensitivity of immunoglobulin genes: changes associated with rearrangement. - Mather, E L (1983)
Immunoglobulin V kappa genes are transcriptionally silent in their germline context and become transcriptionally active upon fusion to the J kappa-C kappa region (kappa locus). To elucidate the role of chromosomal structure in this regulatory phenomenon we have investigated the DNase I sensitivity and methylation status of the kappa locus and selected V kappa genes in a variety of alleles exhibiting different rearrangement configurations and different levels of transcriptional activity. Our findings indicate that the kappa locus in either germline or rearranged contexts maintains a distinctive DNase I-sensitive, hypomethylated structure in plasmacytomas and hybridomas, irrespective of its level of transcriptional activity. In contrast, the germline V kappa genes are in less accessible regions of chromatin and more highly methylated regions of DNA. Upon fusion to the kappa locus, V kappa genes become DNase I-sensitive and hypomethylated. This effect extends several kilobases upstream of the transcriptional initiation site but does not extend to the adjacent V kappa gene or to the identical V kappa allele on the other chromosome, indicating that the structural alteration is a localized cis-acting phenomenon.